Nursing Staff's Perception of Spiritual Care on Haematology, Oncology and Elderly Care Wards. (8th February 2017) - Neary, Wanda; Hillier, Valerie; Fraser, Derek
Abstract : A mixed quantitative/qualitative study using two questionnaires was undertaken, to explore nurses' attitudes to and their perceptions of the concepts of spirituality and spiritual care and to determine whether they believed they could meet patients' needs in this field. Following ethical approval, the questionnaires were distributed to 68 nurses on the Haematology, Oncology and Elderly Care wards. Analyses included descriptive statistics and Cronbach's alpha, and content analysis of open text. A response rate of 52.9% was obtained. Nurses indicated a broad understanding of spirituality, not only one related to religious beliefs and practices. The majority (89.9%) believed that patients should receive spiritual support as part of their holistic care, and 55.6% reported that they could o er this. Content analysis identified key themes relating to spiritual care and to spirituality. A need for further training in spiritual care was recorded by 58.3% of respondents. Further studies concentrating on nurses treating patients with a poor prognosis would be helpful.